قيادة كياهي الحاج أحمد غزالي سالم ودوره في تعليم اللغة العربية بجزيرة مادورا - نينجسيه, ويويك فراستيو; محمودة, أمي (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
Arabic teaching, since its inception, has been exposed to many problems that teachers have faced. These problems are either related to the students’ interest to learn the Arabic language or related to the difficulties of creating the linguistic environment, and etc. The teacher was able to use various of learning media and methods to solve the problems in the educational process. The teacher also can imitates from another experiences and follow their method, and Kiai Haj Ahmad Ghazali Salim has big influence in teaching the Arabic language on the island of Madura. This research is qualitative research. Which is the purposes of this research are knowing type  of leadership of Kiai Haj Ahmad Ghazali Salim and knowing role of his Arabic teaching. The results of this research are the type of leadership of Kiai Haj Ahmad Ghazali Salim are transformational leadership. And he has big influence in Arabic teaching such as creating Arabic language enviroment in Darullughah wa Dirasatil Islamiyah College and many islamic colleges especially in Madura Island.   إن تعليم اللغة العربية منذ نشأته تعرض لكثير من المشاكل التي واجهته المعلمون. وهذه المشاكل أما متعلقة برغبة الطلبة في تعليم اللغة العربية أو متعلقة بصعوبات تكوين البيئة اللغوية، وما أشبه ذلك. واستطاع المعلم أن يستخدم مختلف الوسائل والطرق في بحث المشاكل التي واجهته في عملية التعليمية. كما استفاد المعلم من الخبرات السابقة التي اكتسبها من العرف والتقاليد، كما أن كياهي الحاج أحمد غزالي سالم له دور كبير في تعليم اللغة العربية في جزيرة مادورا. هذا البحث هو بحث نوعي حيث يهدف هذا البحث لكشف أسلوب قيادة كياهي الحاج غزالي سالم وكشف دوره  في تعليم اللغة العربية في جزيرة مادورا. ونتائج من هذا البحث هي كانت القيادة كياهي الحاج أحمد غزالي سالم هي من نوع القيادة التحويلية وله دور كبير هام في تعليم اللغة العربية منها تأسيس المركز اللغة العربية في معهد دار اللغة ودراسة الإسلامية وفي معاهد الإسلامية بجزيرة مادورا.